If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(k+1)+7k=2(4+5k)-3
We move all terms to the left:
3(k+1)+7k-(2(4+5k)-3)=0
We add all the numbers together, and all the variables
3(k+1)+7k-(2(5k+4)-3)=0
We add all the numbers together, and all the variables
7k+3(k+1)-(2(5k+4)-3)=0
We multiply parentheses
7k+3k-(2(5k+4)-3)+3=0
We calculate terms in parentheses: -(2(5k+4)-3), so:We add all the numbers together, and all the variables
2(5k+4)-3
We multiply parentheses
10k+8-3
We add all the numbers together, and all the variables
10k+5
Back to the equation:
-(10k+5)
10k-(10k+5)+3=0
We get rid of parentheses
10k-10k-5+3=0
We add all the numbers together, and all the variables
-2!=0
There is no solution for this equation
| 10x-89+4x=79 | | --(8n-2)=3+10(1-3n) | | 0.5(4x-8)+4=12x-(x+4) | | m^2=-12m+83 | | j-987=-312 | | 2=0.1x | | -5.03+10.9u=1.8u-6.61-6.7u | | 4d+d+5=3d-3 | | 12x-8x-36=20 | | 12x-8x-36=50 | | 7y+44=4(y+8) | | 4n+-1=6n+8-8n+15 | | 8a/9=3a-171 | | -31+6x-3x=8 | | -3b-1=9+7b | | t-112=281 | | -13x+20=-11x+30 | | 12b+24b=15 | | 3/8=3.30x | | 11.73+16.8f=4.1f-15.79+9.5f | | 2(3x+6)=3(7x+4) | | -5=0.6*h | | -2z-6=-z | | −0.4(x−3.8)=−2 | | 6+6n=-6(2n-1)-7n | | −18p=38p | | 5.6-2.4x=7.2 | | -2q-20-20q=20-14q | | 7x+5=-6+4x+20 | | 3-5(6-8p)=-267 | | 5w+12-11w=4w-8 | | 15/d=7 |